Fundamental understanding of in-situ transesterification of microalgae biomass to biodiesel: A critical review. (15th October 2022) - Tien Thanh, Nguyen; Mostapha, Marhaini; Lam, Man Kee; Ishak, Syukriyah; Kanna Dasan, Yaleeni; Lim, Jun Wei; Tan, Inn Shi; Lau, Sie Yon; Chin, Bridgid Lai Fui; Hadibarata, Tony
Graphical abstract: Highlight: Microalgae biomass is identified as a feasible feedstock for biodiesel production. Process parameters of in-situ transesterification from microalgae was reviewed. In-situ transesterification from wet paste microalgae shows promising results. Reaction conditions of in-situ transesterification affect the biodiesel composition. Reaction kinetics and thermodynamic of in-situ transesterification was reviewed. Abstract: One-step in-situ transesterification has been recognized as an alternative approach to produce biodiesel from microalgae biomass. Based on technoeconomic perspective, in-situ transesterification of microalgae is more energy efficient than the conventional two-step process and thus economically competitive for biodiesel production. However, a comprehensive review on the effect of processing parameters towards conversion efficiency of microalgae biomass to biodiesel via in-situ transesterification is still lacking in the literature. Therefore, this review was intended to deliberate on fundamental understanding of this technology, including the effect of different reaction parameters towards biodiesel yield, technoeconomic impact of using wet paste microalgae, biodiesel composition profiles, and the state-of-the-art of the process. Besides, reaction kinetic and thermodynamics aspect of in-situ transesterification from microalgae were also discussed in detail. This review also provided in-depth information for process design and intensification under dedicated in-situ transesterification reaction condition for sustainable biodiesel production. Concurrently, research gaps in in-situ transesterification process was addressed for future study.